Modeling Risk of Soil Erosion in High and Medium Rainfall Zones of Pothwar Region, Pakistan: Assessment of Soil Erosion Risk - Ashraf, Arshad; Abuzar, Muhammad Khubaib; Ahmad, Bashir; Ahmad, Muhammad Munir; Hussain, Qurban (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Soil erosion is a major escalating problem effecting agriculture and water resource development in the Himalayan region. An integrated approach of using Revised Universal Soil Loss Equation (RUSLE) model and Geoinformatic techniques was adopted to assess risk of soil erosion in the Rawal and Ghabbir watersheds lying in the high and medium rainfall zones of Pothwar region, respectively. In Rawal watershed, high (soil erosion rate within 30-100 tons/ha/yr) and very high (>100 tons/ha/yr) risk zones of soil erosion were predicted over 3% and 2% areas, respectively. In Ghabbir watershed, high and very high risk zones were estimated over 29% and 14% areas, respectively. Soil erosion under various slope and land use classes was relatively higher in the Ghabbir than in the Rawal watershed, because of low and sparse vegetative grown under low rainfall condition in the former watershed. Rapid increase in urban development accompanied with loss of vegetation cover is critical in causing high risk of soil erosion in the Rawal watershed. The menace of soil erosion can be prevented through afforestation in various risk prone areas, together with, provision of adequate control over illegal wood cutting and overgrazing in the watersheds. In the gully and slopy areas, check dams and micro-catchments may be developed to control soil loss, which eventually provide suitable vegetative protection in the long run.